Viral clearance is associated with improved insulin resistance in genotype 1 chronic hepatitis C but not genotype 2/3. Issue 1 (26th August 2011) - Thompson, Alexander J; Patel, Keyur; Chuang, Wan-Long; Lawitz, Eric J; Rodriguez-Torres, Maribel; Rustgi, Vinod K; Flisiak, Robert; Pianko, Stephen; Diago, Moises; Arora, Sanjeev; Foster, Graham R; Torbenson, Michael; et al.
Abstract : Objectives: Genotype-specific associations between hepatitis C virus (HCV) and insulin resistance (IR) have been described, but a causal relationship remains unclear. This study investigated the association between a sustained virological response (SVR) and IR after chronic HCV therapy. Methods: 2255 treatment-naive patients with chronic HCV genotype 1 or 2/3 were enrolled in two phase 3 trials of albinterferon alpha-2b versus pegylated interferon alpha-2a for 48 or 24 weeks, respectively. IR was measured before treatment and 12 weeks after treatment using homeostasis model assessment (HOMA)-IR. Results: Paired HOMA-IR measurements were available in 1038 non-diabetic patients (497 with genotype 1; 541 with genotype 2/3). At baseline the prevalence of HOMA-IR >3 was greater in patients with genotype 1 than 2/3 (33% vs 27%; p=0.048). There was a significant reduction in the prevalence of IR in patients with genotype 1 achieving SVR (δ 10%; p<0.001), but not in genotype 1 non-responders or those with genotype 2/3. Multivariate analysis indicated that SVR was associated with a significant reduction in mean HOMA-IR in patients with genotype 1 (p=0.004), but not in those with genotype 2/3, which was independent of body mass index, alanine transaminase, γ-glutamyl transpeptidase and lipid level changes. Conclusions: SVR is associated with a reduction in HOMA-IR in patients with HCV genotype 1 but not in those with genotype 2/3. Genotype 1 may have a direct effect on the development of IR, independent of host metabolic factors, and may be partially reversed by viral eradication.